Older lesbians receiving home care: formal and informal dimensions of caregiving. (4th March 2018) - Butler, Sandra S.
ABSTRACT: Older lesbians face the triple jeopardy of ageism, sexism, and heterosexism, and their experiences are largely invisible. This qualitative, exploratory study examines the formal and informal caregiving experiences of 20 lesbians, 65 and older, who had utilized home care services due to acute illness or chronic disabilities. Half of those not partnered reported some level of isolation from support networks. Nearly all study participants eventually found home care workers with whom they were satisfied and even quite connected. Practice implications are discussed in context of study participants' views of how being lesbian affects their aging process and day-to-day lives.